PENGARUH DYMETIL ESTER PADA BIOSOLAR TERHADAP UNJUK KERJA MOTOR DIESEL SATU SILINDER PADA SUHU PEMANASAN BAHAN BAKAR 95 oC - Rohmat, Yusup Nur; Kusnandar, Kusnandar; Saputro, Rizki Adila (P3M Politeknik Negeri Indramayu, 2018)
The depletion of petroleum reserves makes the emergence of a variety of alternative energy, one of which is Biodiesel. Biodiesel is a fatty acid ester derived from vegetable oil or animal by transesterification or esterification reaction. The purpose of this study was conducted to determine the effect of the use of fuel mixture of biodiesel jelantah with heating 950C to power, torque and Sfc. The test is done by loading the lamp load from 200 - 3200 watt on variation of biodiesel fuel volume by 30%, 40% and 50%. The research method used is descriptive analysis where the result of research is described and described based on research result. From the test results resulted in the addition of biodiesel jelantah fuel effect on power, torque and Sfc generated diesel motor.